A Study of Curriculum Contents of the Master of Science of Medical Parasitology and its Arrangement from the Point of View of Professors - Davood Jabbari-Gharebagh; Aram Feizi; Mousa Jabbari; Mohammad Sadegh Dehghan (Kerman University of Medical Sciences, 2017)
Background & Objective: The curriculum of the Master of Science in parasitology was initially prepared in 1984 and was reviewed in 2001 and 2010 Considering the development of medical technology requirement of society and the necessity of curriculum revision The present study was conducted with the aim to assess the curriculum contents of the Master of Science of parasitology Methods: This descriptive study was conducted in two stages In the first stage university professors were asked to give their opinions concerning the need for curriculum revision (addition or elimination of courses) in this field In the second stage based on the findings of the first stage and the current curriculum a questionnaire was prepared and was distributed among the professors through email Then 30 completed questionnaires were evaluated Based on the criteria of compulsory courses prerequisite or compensatory courses and importance of the courses data analysis was performed in EXCEL software and the results were reported in the form of descriptive statistics Results: After summarizing the comments and verifying the compliance of the currently approved curriculum courses with those proposed by participants the addition of the prerequisite courses of New technologies of parasite detection and Taxonomy and the compensatory courses of Biotechnology Technical language Geography of parasitic diseases in Iran Bioinformatics and Teaching methods was proposed Moreover the elimination of the courses of Preliminary bacteriology Histology of the human body Clinical biochemistry Basic genetics Preliminary hematology and Principles of health services was proposed Conclusion: Based on the results of this study among the 10 currently approved prerequisite courses 8 are necessary and desirable in the view of the participants However the compensatory courses require modification